A to z of akhlaaq; moral values for children - Khan, Nafees (Goodword Books India, 2002)
"A to Z of Akhlaaq" is a guide that explores the principles of good character and ethical behavior in Islam. Each letter corresponds to a specific virtue or moral quality, such as honesty, kindness, and patience. The book aims to instill these values in readers, encouraging them to embody these traits in their daily lives and interactions, fostering a strong moral foundation rooted in Islamic teachings.